KEPEMILIKAN MANAJER, KEPUTUSAN PENDANAAN, DAN FAKTOR LAIN YANG MEMENGARUHI NILAI PERUSAHAAN NON KEUANGAN - Ignes Januar Cahyadi; Buha Johan Pande F.S (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to determine and examine factors influencing firm value consisting of several variables including managerial ownership, financing decisions, liquidity, profitability, firm size, investment decisions, corporate activity, and dividend policy This study used 46 non-financial companies listed on the Indonesia Stock Exchange. Each company is chosen using purposive sampling method in period 2014-2016. The hypothesis in this research are analyzed using multiple linier regression analysis method in the research model. The results of this study show that managerial ownership, financing decisions, profitability, investment decisions, and dividend policy had influence towards firm value whereas liquidity, firm size, and corporate activity had no influence towards firm value.